2021
DOI: 10.1007/s00227-021-03895-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary analysis of two sympatric marine turtle species in the eastern Mediterranean

Abstract: Dietary studies provide key insights into threats and changes within ecosystems and subsequent impacts on focal species. Diet is particularly challenging to study within marine environments and therefore is often poorly understood. Here, we examined the diet of stranded and bycaught loggerhead (Caretta caretta) and green turtles (Chelonia mydas) in North Cyprus (35.33° N, 33.47° E) between 2011 and 2019. A total of 129 taxa were recorded in the diet of loggerhead turtles (n = 45), which were predominantly carn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 87 publications
1
7
0
Order By: Relevance
“…Similar frequencies for Holothuroidea (3.3%) were found by Karaa et al ., 2018, after performing necropsies on 132 loggerheads from the Gulf of Gabes, Tunisia. Further reports can be also found in Palmer et al ., 2021, where also a photograph of a possibly intact sea cucumber recovered from a turtle’s ingestive tract is provided.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar frequencies for Holothuroidea (3.3%) were found by Karaa et al ., 2018, after performing necropsies on 132 loggerheads from the Gulf of Gabes, Tunisia. Further reports can be also found in Palmer et al ., 2021, where also a photograph of a possibly intact sea cucumber recovered from a turtle’s ingestive tract is provided.…”
Section: Discussionsupporting
confidence: 61%
“…Similar frequencies for Holothuroidea (3.3%) were found by Karaa et al, 2018, after performing necropsies on 132 loggerheads from the Gulf of Gabes, Tunisia. Further reports can be also found in Palmer et al, 2021, where also a photograph of a possibly intact sea cucumber recovered from a turtle's ingestive tract is provided. This relatively low frequency of consumption of sea cucumbers reported in the above studies, reflects the rarity of observations of this consumption in our study site.…”
Section: Discussionmentioning
confidence: 99%
“…6E, F; Forster unpubl. ; Palmer 2021). These observations highlight the extent of nutrient transfer and food web structuring by migratory insects and hint at the importance of these transient events for linking geographically separated ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…The stranding events recorded in the current study likely represent a small percentage of the number of beetles migrating, suggesting that large quantities of nutrients from the beetles' bodies could end up in the sea and, therefore, be available for the marine ecosystem. For example, autopsies performed on loggerhead and green turtles during spring 2019 revealed that migratory invertebrates, such as painted lady butterflies ( Vanessa cardui ) and migratory Orthoptera, had been ingested (Palmer et al, 2021). Other marine residents, such as fish and marine invertebrates, no doubt also feed on the migrant insects falling into the ocean.…”
Section: Discussionmentioning
confidence: 99%